Massive seed predation of Pseudobombax grandiflorum (Bombacaceae) by parakeets Brotogeris versicolurus (Psittacidae) in a forest fragment in brazil - Francisco, M. R.; Lunardi, V. D.; Galetti, M. (Associação Tropical Biology Inc, 2002)
Here we report massive seed predation of Pseudobombax grandiflorum (Bombacaceae) by Botogeris versicolurus (Psittacidae) in a forest fragment in Brazil. The intensity of seed predation was very high when compared to other studies in continuous forest, perhaps resulting from a scarcity of resources in such areas. This scarcity may limit the range of parrot's diet to a few plant species. It suggests that studies of Psittacidae seed predation may be important for conservation of some plants in fragments.
Keywords: Atlantic forest; Brazil; brotogeris versicolums; forest fiagmentation; Pseudobombax grandiflorum; Psittacidae; seed predation